ANALISIS PENGARUH PENGARUH FINANCING TO DEPOSIT RATIO, NON PERFORMING FINANCING, SPREAD BAGI HASIL DAN TINGKAT BAGI HASIL TERHADAP PEMBIAYAAN BAGI HASIL (Studi pada Bank Umum Syariah di Indonesia Periode Tahun 2008-2013) - Prasasti, Devki; Prasetiono, Prasetiono (Diponegoro Journal of Management, 2014)
This study aims analyze the factors that affect profit and loss sharing financinng. The purpose of this study was to analyze the influence of Financing to Deposit Ratio, Non Performing Financing, equivalent rate of profit sharing and spread profit sharing of profit and loss sharing financing. The samples used are selected using purposive sampling technique and only 4 banks in accordance with the criteria. The data is taken from the Quarterly Financial Reports Sharia Bank in Bank Indonesia's website during the period of 6 years from 2008 to 2013. The data collected were analyzed using descriptive statistics and multiple regression analysis. The results showed that the coefficient of determination through the four test variables: Financing to Deposit Ratio, Non Performing Ratio, equivalent rate of profit sharing and spread profit sharing can explain the variation in the dependent variable for profit and loss sharing financing by 89% while the rest is explained by other causes beyond the research variables . Four variables simultaneously affect the results because the financing for the significance level of less than 0.05. From the partial results only variable non-performing ratio has negative significant affect to profit and loss sharing financing, while the other three variables Financing to Deposit Ratio, equivalent rate of profit sharing and spread profit sharing have positive significant affect to profit and loss sharing financing.